PERAN KELOMPOK TANI DALAM PENGEMBANGAN PADI ORGANIK MENUJU PASAR TERSTRUKTUR (Studi Kasus di Kabupaten Bandung) (Jurnal Social Economic of Agriculture, 2016)
Demand for rice continues to increase, including demand for organic rice. Seeing the high level of demand for organic rice, the government responded by facilitating and supporting facilities and infrastructure in the production process of organic rice. Government response and support is realized by a group approach, so that farmers enjoy farming with good results. The number of farmer groups in Bandung regency until the year 2012 was 1782 group. But the reality, part of the results received are not enjoyed by members of the group. The purpose of this study was to determine: 1) The process of the growth of farmers' groups; 2) The role of the farmer group in development the market for organic rice. The study was conducted in Nurani Sejahtera farmers group ,Bandung regency. This research was a qualitative with case study technique. Informants in this study were the chairman and members of Nurani Sejahtera farmers groups, consumers of organic rice and Bandung District Agriculture Office. Data were analyzed descriptively. The results showed that although the Nurani Sejahtera Farmers Group was formed at the instigation of the government, but the member aware of the importance of the group. Overall Nurani Sejahtera farmer groups already play a role in maintaining the quantity, the quality of grain (by strengthening the capacity of production), and the sustainability of products through maintaining harmony with the members and with the market. Clarification always done related to product information and market information, so that members feel satisfied and believe what is done by the group.